Word Choice and Language Style of the Novel ‘Rahwana Putih' in Improving 21st Century Student Literacy - Herawati, Nanik; Setiyadi, Dwi Bambang Putut; Hersulastuti; Santoso, Gunawan Budi; Widayanti, Sukasih Ratna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The lack of students' ability to understand literacy in novels. This problem reflects the low interest of students in learning Indonesian and their difficulties in understanding literary works containing complex language. With the analysis of lexical choices and language styles in the novel